Limitations and insights regarding atmospheric mercury sampling using gold - Gačnik, Jan; Lyman, Seth; Dunham-Cheatham, Sarrah M.; Gustin, Mae Sexauer (Analytica chimica acta, 2024)
Atmospheric mercury (Hg) concentrations are quantified primarily through preconcentration on gold (Au) cartridges through amalgamation and subsequent thermal desorption into an atomic fluorescence spectrometry detector. This procedure has been used for decades, and is implemented in the industry-standard atmospheric Hg analyzer, the Tekran 2537. There is ongoing debate as to whether gaseous elemental mercury (Hg0) or total gaseous mercury (TGM, Hg0 + HgII) is measured using Au cartridges. The raw Hg signal processing algorithms for the Tekran 2537 analyzer have also been questioned. The objective of this work was to develop a better understanding of what forms of Hg are collected on gold cartridges through the use of permeation tube-based calibrators, that release known amounts of Hg0 and HgII. The potential differences between different Tekran analyzer models (i.e., 2537B versus 2537X) Hg signal processing algorithms, and Hg0 calibration methods were also investigated. Experiments were performed using Hg0 and HgII permeation calibrators. Validation tests showed that the HgII calibrator produced a reproducible and stable HgII permeation rate (2.2 ± 0.2 pg min−1). Results of HgII sampling and analysis using Au amalgamation showed the gold cartridges measured up to 75 % HgII, with the value at the beginning of the HgII measurement being much lower (as low as 10 %) due to HgII adsorption on analyzer surfaces and the Tekran particulate filter. Furthermore, thermal desorption of Hg from Au reduced only 80 % of HgII to Hg0, resulting in additional HgII that was not measured by the analyzer. By adding a thermolyzer upstream of the analyzer, 97 % of HgII was measured as Hg0. Additionally, Hg0 measurements using Tekran 2537 B and X models using a newly developed signal processing algorithm, different peak integration methods, and two Hg0 sources were compared. Results showed the 2537X model was not affected by the integration type, while the 2537B model was. Bell jar calibration based on the Dumarey equation resulted in 6 % ± 7 % (mean ± SD) underestimation of measured Hg0 concentrations compared to the calibration with a permeation calibrator. Gold cartridges measured an atmospheric Hg fraction somewhere between Hg0 and TGM due to HgII adsorption and inefficient reduction of HgII to Hg0 during thermal desorption from Au. Since HgII in ambient air can be 25 % of total Hg, distinguishing between Hg0 and TGM is important. The use of a thermolyzer or a cation exchange membrane upstream of gold cartridges is recommended to enable TGM or Hg0 measurements, respectively. Observations showed that traceable multipoint calibrations of atmospheric Hg measurements are needed for Hg quantification, and that different Hg0 calibration methods can produce significantly different results for measured atmospheric Hg concentrations. [Display omitted] •Gold amalgamation procedure measures a Hg fraction in between Hg0 and TGM.•10–75 % of HgII is recovered as Hg0 by the Tekran 2537 analyzer.•HgII is lost through adsorption and inefficient thermal desorption of Hg from gold.•Thermolyzer quantitatively converted HgII to Hg0 to enable a TGM measurement.•Tekran 2537B models measured 1.5 times higher Hg concentrations than 2537X models.